Barriers to Health Service Access: A Study on Conditioning Factors of Self-Health and Illness Perception in Argentina - Marin, Gustavo Horacio (2021)
Aims: To determine self-health image and illness perception as potential barriers to health services access among inhabitants of La Plata, Buenos Aires, Argentina. Methods: A cross-sectional study, where survey, “Brief IllnessPerception Questionnaire” and basic medical examination were performed on 2430 participants at homes. Results: Although men showed a better concept of their state of health, they perceived their illness worse and belatedly. Only 45% of participants perceived symptoms disease, and from them, 48% finally decided to consult to the health system. Hence, from every 100 sick people, only 21 had access to a health institution. Higher level of education achieved, better socio-economic conditions or holding health insurance were significantly associated with appropriate health seeking, and access to health service. Conclusions: Self-health image and disease perception affected people’s access to health services. Participants of this study showed suboptimal disease perception, manifested as meager and delayed demand for care. These results demonstrate the weakness of current health care model based on people’s spontaneous demand. It is necessary to adopt a new health system for the entire population, regardless of the self-awareness that people may have about their own health/disease status. It would be a more inclusive, effective and efficient healthcare model.